Immunological Responses to Helminths and HIV-1 CoInfections - Chavura, Elton; Singini, Wales; Chidya, Russel; Mbakaya, Balwani Chingatichifwe (European Scientific Journal, ESJ, 2023)
Aim: Helminth infections result from poor sanitation. We evaluated the effect of helminth infections on HIV disease progression through the monitoring of 2 outcomes: (1) plasma HIV-1 RNA Viral load (V/L) and (2) Cluster of Differentiation (CD4+) T-lymphocyte count amongst helminth-HIV-1 co-infected persons. We hypothesized that (1) concurrent helminth infections compromise immune control, resulting in rising VL and reduced CD4+ T-lymphocyte count (2) and that, subject to successful treatment, a decrease in plasma VL could slow down disease progression. Methods: We reviewed 2032 citations, evaluated 432 abstracts, and included 10 articles according to the PRISMA diagram. The methodologies were appraised using a Mixed Method Appraisal Tool (MMAT). Results: At enrolment, plasma VL was significantly higher in individuals with helminths (5.01 log10 vs. 3.41 log10, p < 0.001). The effective range was 5.28 log10 copies/mL at baseline and 4.67 log10 copies/mL, (p < 0.05) after treatment and a trend for 0.61 log10 lower VL. Significant interactions were seen in the successfully treated groups (p < 0.001). CD4+ T-lymphocyte count values were not significantly different in the co-infection groups relative to those with HIV infection alone. Conclusion: Helminths and HIV-1 co-infections are associated with an increase in HIV-1 RNA levels that accelerate the progression of the sub-clinical disease to symptomatic AIDS.